Implementation Of Independent Learning Curriculum Management In Improving Student Competence - Nurlaela Nurlaela; Noviliatun Noviliatun; Luthfi Nur Azizah; Nur Khofifah; Fatimah Az Zahro (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
This study aims to examine the administration of the Independent Curriculum at SMAIQu Al-Bahjah Cirebon, which includes elements of planning, organization, implementation , and evaluation . Data collection methods for this qualitative study include observation, interviews, and documentation, all of which are descriptive approaches. The findings indicate that curriculum development at the Islamic boarding school is carried out contextually by combining Islamic values and student characteristics. The Pancasila Student Profile Strengthening Project (P5) and intracurricular activities are used in the implementation of learning to combine academic and character development. However, during the evaluation process, challenges remain, especially those related to the distribution of teacher skills. in developing learning materials and assessment systems. Therefore, the administration of the Independent Curriculum has been running quite well, but it needs to focus on improving the evaluation component and continuing to raise teacher skill standards.